A Fully Secure KP-ABE Scheme on Prime-Order Bilinear Groups through Selective Techniques. (29th November 2020) - Obiri, Isaac Amankona; Xia, Qi; Xia, Hu; Obour Agyekum, Kwame Opuni-Boachie; Asamoah, Kwame Omono; Sifah, Emmanuel Boateng; Zhang, Xiaosong; Gao, Jianbin
Abstract : Key-policy attribute-based encryption (KP-ABE) is the cryptographic primitive which enables fine grained access control while still providing end-to-end encryption. Although traditional encryption schemes can provide end-to-end encryption, users have to either share the same decryption keys or the data have to be stored in multiple instances which are encrypted with different keys. Both of these options are undesirable. However, KP-ABE can provide less key overhead compared to the traditional encryption schemes. While there are a lot of KP-ABE schemes, none of them simultaneously supports multiuse of attributes, adaptive security, monotone span programs, and static security assumption. Hence, we propose a fully secure KP-ABE scheme for monotone span programs in prime-order group. This scheme uses selective security proof techniques to obtain the requisite ingredients for full security proof. This strengthens the correlation between selective and full security models and enables the transition of the best qualities in selective security models to fully secure systems. The security proof is based on decisional linear assumption and three-party Diffie–Hellman assumption.